Cocoa farmers’ perceptions of relationship between transfer of technology skills, human resource development skills and extension agents’ work performance in peninsular Malaysia - Motolani, Mohd Mustafa Munim (2021)
The aim of this study to identify the relationship between extension agent’s (EA) skill of transfer of technology (ToT) and human resource development (HRD) to the work performance (WP) that significantly contributed to the low productivity of cocoa bean from the Malaysian cocoa smallholders. The contribution of extension agents skills are considered crucial in transferring technology to the farmers. The study identify skill level of extension agents’ on ToT and HRD and WP to productive cocoa farmers (PCFs) in Peninsular Malaysia. It’s also determined the relationship between extension agents’ skills and work performance and identifies the most important factor contributed to work performance. The study employed stratified random sampling technique. A total of 353 PCFs were sampled to evaluate the skills of the extension agents’ through the use of structured questionnaires to elicit response from the farmers. The data were analysed using descriptive statistics and Pearson correlation analysis. The skill levels of cocoa extension agents’ in Peninsular Malaysia in ToT and HRD have a high skill level. Based on high level skill in ToT and HRD, work performance was evaluated at high level also. Significant correlation (p<0.01) existed between competencies (ToT and HRD) and extension agents’ performance. Multiple regression analysis results showed that technical skills (p=0.030), leadership skills (p=0.005), decision making support skills (p=0.048) and social skills (p=0.000) are positive and significant (p<0.05) determinants, while technology delivery skills (p=0.424) and technology evaluation skills (p=0.063) do not contribute significantly towards extension agents’ performance. The result shows the social skills attributed the bigger Beta value (.266) and the most contribution to extension agents’ work performance. Technical skills, leadership skills, decision making support skills and social skills are four significance values from the competencies component interpreted the 63.0 percent (Adj. R2 value) contributing to the extension agents’ work performance. There is therefore needs to create future development plan to increase competency level of the extension agents’, particularly in the area of transfer of technology skills. Function of ToT and HRD reflected work performance achievement to increase the smallholder potential and be able to empower them to increase cocoa production.